DEP regimen for the treatment of hemophagocytic lymphohistiocytosis: a review of published experience - Meng, Guangqiang; Feng, Saran; Wang, Yan (Frontiers in Pharmacology, 2025)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyper-inflammatory clinical syndrome characterized by a storm of inflammatory factors. In the treatment of HLH, it is critical to provide active and effective treatment immediately and hamper the inflammatory cytokine storm in a timely manner to improve patient symptoms. Currently, the first-line treatment for HLH is still based on etoposide and glucocorticoids. Unfortunately, the treatment effect of HLH remains insufficient, the mortality rate of patients remains high, and the prognosis remains poor. Therefore, effective salvage treatments are urgently needed to alleviate relapsed and refractory HLH. More than 10 years have passed since the liposomal doxorubicin combined with etoposide and methylprednisolone (DEP) regimen was first reported as a salvage treatment for HLH. In more than 10 years of clinical practice, many studies have reported the effectiveness and safety of the DEP regimen for the treatment of HLH. The DEP regimen not only demonstrated a good salvage treatment effect in relapsed refractory HLH but also revealed an optimal therapeutic effect in first-line induction treatment of HLH.